MicroMundo Upside Down: Targeted Searching for Antibiotics-Producing Bacteria From Soil With Reverse Antibiosis Approaches - Alvarado, María; Clemente-Casares, Pilar; Moreno, Diego A.; de Groot, Piet W. J. (Frontiers in Microbiology, 2020)
Tiny Earth is a popular international citizen science program aimed at improving public awareness on the growing antimicrobial resistance problem of which MicroMundo Albacete is a Spanish node. With a protocol that is focused on the isolation of antibiotics-producing actinomycetes from soil, 70% of the high school students in MicroMundo Albacete 2020 isolated colonies with antagonistic activity against Gram-positive tester bacteria. However, no activity was found against Gram-negative bacteria. Here, we further adapted the protocol towards a more targeted screening that also enables isolation of antagonistic bacteria against Gram negatives using two different reverse-antibiosis approaches involving a spraying technique or flipping soil sample discs upside down. Exploiting the soil samples from MicroMundo Albacete 2020, the new approaches yielded isolation of actinomycete bacteria with antagonistic activity against Gram-negative as well as Gram-positive tester bacteria. We propose that (educational) science programs which aim to search for antibiotic-producing bacteria may implement these approaches in their protocol to promote a successful and stimulating outcome of the experiment for the participating students.